Pathway analysis of yield components in several New Plant Type (NPT) rice genotypes - DULBARI DULBARI; DESTIEKA AHYUNI; FAJAR ROCHMAN; RIZKY RAHMADI; PRIYADI PRIYADI; SUBARJO SUBARJO; LINA BUDIARTI; HIDAYAT SAPUTRA; MOH. HARIS IMRON S. JAYA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Dulbari, Ahyuni D, Rochman F, Rahmadi R, Priyadi, Subarjo, Budiarti L, Saputra H, Jaya MHIS. 2025. Pathway analysis of yield components in several New Plant Type (NPT) rice genotypes. Biodiversitas 26: 770-777. Rice is essential for global nutrition, especially in Asia, with increasing production needed to meet rising food demands from population growth. Efforts to increase rice production are carried out through plant breeding programs. Grain weight per panicle is one of the yield components in rice plants that significantly determines production. Despite its importance, its influence in the selection process is not independent, as it is closely associated with other traits, either directly or indirectly. Therefore, this study aimed to determine the relationship between yield components and their direct and indirect effects on grain weight per panicle of several new plant types (NPT) of rice varieties grown in 2 different locations, namely Tanggamus and Lampung Timur. The study procedures were conducted using a Randomized Complete Block Design with 12 genotypes and 3 replications. Genotypes consisted of 10 NRTs, including IPB 3S, IPB 4S, IPB 5R, IPB6R, IPB117-F-7-2-1, IPB 117-F-7-7-1, IPB 117-F-14-4-1, IPB 117-F-15-4-1, IPB 117-F-20-1-1, IPB 117-F-80-2-1. Meanwhile, the 2 control varieties included Ciliwung and Ciherang. The results showed that rice grain weight per panicle significantly correlated with the number of productive tillers, panicle length, number of filled grains per panicle, and percentage of filled grains per panicle. Productive tiller number, panicle length, number of filled grains per panicle, and percentage of filled grains per panicle directly and indirectly affected grain weight per panicle. In addition, the number of filled grains per panicle directly influenced 0.49%.